Performance Modelling of Dual Air/Water Collector in Solar Water and Space Heating Application - Viacheslav Shemelin; Tomas Matuska (International Journal of Photoenergy)
In the present work, the detailed mathematical model of a dual air/water solar collector (DAWC) has been developed and experimentally verified. To demonstrate the application of the DAWC, three buildings with different energy performance levels and three building locations were chosen in analyzed case studies. Four solar collector systems were compared with one another. The solar yield of the described systems was determined by simulation using the detailed theoretical model of DAWC. The results indicate that in the case of combining a domestic hot water preparation system and recirculating-air heating system based on DAWC, it is possible to achieve up to 30% higher solar energy yield compared to a conventional solar domestic hot water preparation system dependent on climate and building performance.